2021
DOI: 10.1017/cts.2021.821
|View full text |Cite
|
Sign up to set email alerts
|

The Un-meeting approach to stimulate collaborative adult learning: an application for clinical research professionals

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…15,21 Pedagogy Challenge: Rounds are intended to be a learning opportunity, so attendance is most advantageous to RPs and learners from other component teams (eg, newly hired nurses) and less so for nonlearners During rounds, consider conducting pedagogically focused activities when learners are available from more than one component team (eg, RPs and newly hired RNs). 29,30,57,58 Plan meeting schedules and agendas to prioritize the time of team members who are necessary for other meeting processes (eg, informing, deliberating, and strategizing) but may be less likely to benefit from pedagogically focused activities. 1,21,29,30,45,59 Abbreviations: MTS, multiteam system; RN, registered nurse; RP, resident physician.…”
Section: Discussionmentioning
confidence: 99%
“…15,21 Pedagogy Challenge: Rounds are intended to be a learning opportunity, so attendance is most advantageous to RPs and learners from other component teams (eg, newly hired nurses) and less so for nonlearners During rounds, consider conducting pedagogically focused activities when learners are available from more than one component team (eg, RPs and newly hired RNs). 29,30,57,58 Plan meeting schedules and agendas to prioritize the time of team members who are necessary for other meeting processes (eg, informing, deliberating, and strategizing) but may be less likely to benefit from pedagogically focused activities. 1,21,29,30,45,59 Abbreviations: MTS, multiteam system; RN, registered nurse; RP, resident physician.…”
Section: Discussionmentioning
confidence: 99%
“…This is a first attempt to collectively discuss and address issues related to the recruitment and retention of AMC CRPs at the national level. The strength of these data is the breadth of contributions across 35 CTSA hubs who participated in the Collaborative Conversations Un-Meeting sessions between September 2020 and February 2021 [18]. Qualitative research using a cloud-based collaborative platform such as Zoom has been reported as an effective method [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, describing recruitment and retention facilitators and barriers within the clinical research profession at AMCs will highlight the key issues and present common solutions to improving these stages of hiring and maintenance of the CRP workforce. This paper will discuss factors related to the current state of AMC CRP workforce needs related to recruitment, job titles, retention and diversity, as identified through a qualitative analysis of specific workgroup breakout sessions during the CRP Collaborative Conversations Un-Meeting series [18]. Our study aims to provide opportunities for National Center for Advancing Translational Science (NCATS) and AMC policy considerations and guidance regarding institutional improvements to sustainability of the CRP workforce for quality CTR operations.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond direct funding, other types of support for meeting planning and manuscript development can help to continue initial engagement and concept development that occurs during an Un-Meeting. As one example, CLIC has provided logistical and other support for CTSA Program hubs to develop Synergy Papers, with calls for Synergy Papers aligned with Un-Meetings hosted at the CLIC University of Rochester site and encouraged for Un-Meetings supported by CLIC at other hub sites [30][31][32][33]. The Synergy Paper is a collaborative manuscript developed by three or more CTSA Program hubs spanning at least two stages of translational research, with the goal of addressing substantial challenges in clinical or translational research [36].…”
Section: Supporting Teams Following An Un-meetingmentioning
confidence: 99%